Engineered Exosomes for Drug Delivery in Cancer Therapy: A Promising Approach and Application - Fu, Peiwen; Yin, Siqi; Cheng, Huiying; Xu, Wenrong; Jiang, Jiajia (Current Drug Delivery, 2024)
A significant amount of research effort is currently focused on investigating the role of exosomes in various cancers. These tiny vesicles, apart from acting as biomarkers, also play a crucial role in tumor formation and development. Several studies have demonstrated that exosomes can be a drug delivery vehicle for cancer therapy. In this paper, we highlight the key advantages of exosomes as a drug delivery candidate, with a particular focus on their low immunogenicity, natural targeting ability and suitable mechanical properties. Furthermore, we propose that the selection of appropriate exosomes and drug loading methods based on therapeutic goals and product heterogeneity is essential for preparing engineered exosomes. We comprehensively analyzed the superiorities of current drug-loading methods to improve the creation of designed exosomes. Moreover, we systematically review the applications of engineered exosomes in various therapies such as immunotherapy, gene therapy, protein therapy, chemotherapy, indicating that engineered exosomes have the potential to be reliable and, safe drug carriers that can address the unmet needs in cancer clinical practice.
Keywords: gene therapy